2008
DOI: 10.1017/s1368980007001474
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of under- and over-reporters of energy intake among 18–20-year-old males: the Gothenburg Osteoporosis and Obesity Determinants (GOOD) study

Abstract: Objective: To identify and describe characteristics of the bias of reported energy intake of participants in the Gothenburg Osteoporosis and Obesity Determinants (GOOD) study. Design: A validated diet history with a detailed questionnaire and an interview was used. Body fat was analysed by dual-energy X-ray absorptiometry. The ratio of energy intake (EI) to BMR was used to define under-reporters (EI:BMR , 1?30), acceptable reporters (EI:BMR $ 1.30 to ,2.64) and over-reporters (EI:BMR $ 2.64). Setting: Sahlgren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
20
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 21 publications
1
20
1
Order By: Relevance
“…While previous studies have suggested several lifestyle factors as a risk factor of energy over-reporting, including low BMI (3,10,12,14), none of these factors, including weight status, was associated with the risk of an being over-reporter in this study of relatively lean young Japanese women (except for sedentary lifestyle). On this basis, over-reporting may be a random rather than a systematic phenomenon compared with underreporting, in the present population at least.…”
Section: Discussioncontrasting
confidence: 87%
See 4 more Smart Citations
“…While previous studies have suggested several lifestyle factors as a risk factor of energy over-reporting, including low BMI (3,10,12,14), none of these factors, including weight status, was associated with the risk of an being over-reporter in this study of relatively lean young Japanese women (except for sedentary lifestyle). On this basis, over-reporting may be a random rather than a systematic phenomenon compared with underreporting, in the present population at least.…”
Section: Discussioncontrasting
confidence: 87%
“…Consistent with previous Western studies (1,3,7,10,(12)(13)(14)16), energy-adjusted nutrient and food intakes differed among under-, acceptable, and over-reporters of energy intake, although nutrient and food intake in Japanese subjects appears to provide no clue as to whether the diet of under-and over-reporters is healthier or unhealthier than that of acceptable reporters (9,17).…”
Section: Discussionsupporting
confidence: 81%
See 3 more Smart Citations